Can invasions occur without change? A comparison of G‐matrices and selection in the peach‐potato aphid, Myzus persicae. Issue 15 (20th November 2013) - Bacigalupe, Leonardo D.; Barrientos, Karin; Beckerman, Andrew P.; Carter, Mauricio J.; Figueroa, Christian C.; Foster, Stephen P.; Moore, Allen J.; Silva, Andrea X.; Nespolo, Roberto F.
Abstract: Most evolutionary research on biological invasions has focused on changes seen between the native and invaded range for a particular species. However, it is likely that species that live in human‐modified habitats in their native range might have evolved specific adaptations to those environments, which increase the likelihood of establishment and spread in similar human‐altered environments. From a quantitative genetic perspective, this hypothesis suggests that both native and introduced populations should reside at or near the same adaptive peak. Therefore, we should observe no overall changes in theG (genetic variance–covariance) matrices between native and introduced ranges, and stabilizing selection on fitness‐related traits in all populations. We tested these predictions comparing three populations of the worldwide pest Myzus persicae from the Middle East (native range) and the UK and Chile (separately introduced ranges). In general, our results provide mixed support for this idea, but further comparisons of other species are needed. In particular, we found that there has been some limited evolution in the studied traits, with the Middle East population differing from the UK and Chilean populations. This was reflected in the structure of theG ‐matrices, in which Chile differed from both UK and Middle East populations. Furthermore, the amount of genetic variation was massively reduced in Chile in comparison with UK and Middle East populations. Finally, we found no detectable selection on any trait in the three populations, but clones from the introduced ranges started to reproduce later, were smaller, had smaller offspring, and had lower reproductive fitness than clones from the native range. Abstract : Species that live in human‐modified habitats in their native range might have evolved specific adaptations to those environments, which increase the likelihood of establishment and spread in similar human‐altered environments. From a quantitative genetic perspective, this hypothesis suggests that both native and introduced populations should reside at or near the same adaptive peak; therefore, we should observe no overall changes in theG (genetic variance–covariance) matrices between native and introduced ranges, and stabilizing selection on fitness‐related traits in all populations. We tested these predictions comparing three populations of the worldwide pest Myzus persicae from the Middle East (native range) and the UK and Chile (separately introduced ranges).